2020
DOI: 10.1155/2020/9562192
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Azathioprine/6-Mercaptopurine in Children and Adolescents with Inflammatory Bowel Diseases: A Multimethod Study

Abstract: Background. Measurement of the degree of adherence is a key element for the evaluation of treatment efficacy and safety; thus, adherence plays an important role in clinical research and practice. The aim of this study was to investigate medication adherence in children with inflammatory bowel disease (IBD) utilizing a multimethod assessment approach. A further aim was to examine factors that can influence adherence within this population. Methods. Medication adherence in 47 children (age range 3 to 17 years) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
0
5
1
Order By: Relevance
“…To our surprise, parent reported non-adherence (31.37%) was higher than Child self-reported non-adherence (25.00%) in this study, however, the difference being not statistically significant. This was different from the findings of ( Alsous et al, 2020 ), ( Reed-Knight et al, 2011 ), but ( Ingerski et al, 2010 ). Furthermore, it revealed that children reported lower scores for unintentional non-adherence and tended to have higher scores for intentional non-adherence, compared with parent-reported results, but the differences between them were not statistically significant.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…To our surprise, parent reported non-adherence (31.37%) was higher than Child self-reported non-adherence (25.00%) in this study, however, the difference being not statistically significant. This was different from the findings of ( Alsous et al, 2020 ), ( Reed-Knight et al, 2011 ), but ( Ingerski et al, 2010 ). Furthermore, it revealed that children reported lower scores for unintentional non-adherence and tended to have higher scores for intentional non-adherence, compared with parent-reported results, but the differences between them were not statistically significant.…”
Section: Discussioncontrasting
confidence: 99%
“…This is the first study to investigate medication adherence and analyze the predictors of non-adherence to medication in Chinese children with IBD. Our results showed that about a quarter of children with IBD have poor medication adherence, which is higher than the rate in the United States (14.61%–17.47%) ( Greenley et al, 2015 ), but similar to that in South Korea (31.2%) ( Lim et al, 2020 ), lower than that in Jordan and the United Kingdom (36.2%) ( Alsous et al, 2020 ), and much lower than that in Japan (43.0%) ( Tanaka et al, 2021 ). Non-adherence to medication in children with IBD is common worldwide.…”
Section: Discussionmentioning
confidence: 40%
“…In that group, there were five CD and two UC patients. We did not asses the adherence to treatment, using any specific questionnaires, although a multimethod assessment is more widely used [ 3 ]. In the future, we plan to assess adherence not only by objective methods but also with a specific questionnaire for both: parents and children.…”
Section: Discussionmentioning
confidence: 99%
“…Hommel et al, evaluating adherence in 42 IBD adolescents, found that the majority of the sample (93%) had demonstrated quantifiable 6-TGN levels but only 14% were within the therapeutic range what indicated that nonadherence assessment was especially important in the group of adolescents, faced with learning to manage a chronic condition and negotiate normal developmental issues [ 16 ]. Alsous et al [ 3 ], using a binary logistic regression analysis, identified the age to be independently predictive of adherence, with adolescents more likely to be classified as nonadherent. The mean age of our nonadherent subjects was 15 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation